Nurses retention: the impact of transformational leadership, career growth, work well-being, and work-life Balance - Eman Sameh AbdELhay; Samah Mohamed Taha; Mona Metwally El-Sayed; Sahar Hassan Helaly; Islam Sameh AbdELhay (BMC Nursing)
Abstract Background Nurse retention is critical for healthcare systems worldwide, as high turnover rates adversely affect patient care and organizational stability. Aim Examines the impact of transformational leadership, career growth opportunities, work well-being, and work-life balance on nurse retention. Methods A cross-sectional study was conducted with 297 nurses employed in inpatient wards at Mansoura University Hospital. The study measured variables using the Nursing Retention Index, Global Transformational Leadership Scale, Career Growth Scale, Work Well-Being Scale, and Work-Life Balance Scale. Results A linear regression analysis identified significant predictors of nurse retention. Work-life balance was found to be a strong predictor, with an unstandardized coefficient (B) of 0.255 (p < 0.001) and a standardized coefficient (β) of 0.426, indicating a positive relationship with retention, transformational leadership also significantly influenced retention, with a B of 0.082 (p = 0.002) and a β of 0.171. In contrast, Career Growth and Work-Life Balance did not significantly predict retention, showing coefficients of -0.082 (p = 0.154) and -0.042 (p = 0.482). The model explained 23.4% of the variance in nurse retention (R-squared = 0.234) and demonstrated statistical significance (F = 22.294, p < 0.001). Conclusion This study highlights the critical role of transformational leadership and work-life balance in enhancing nurse retention. However, career growth and work well-being did not significantly predict retention in this study. Healthcare institutions should focus on transformational leadership and work-life balance to enhance nurse retention. Future studies should explore factors related to career growth and work well-being to determine their potential impact on retention.